Finding Models in Model-Based Development - , Wolfram Schulte; Jackson, Ethan (Model Driven Engineering Languages and Systems, 2011)
Model-based development focuses on creating and manipulating domain models. We present the formula language and its tool environment for specifying, documenting, and analyzing models.